Incidence and risk of xerosis with targeted anticancer therapies (2015)
Background Many targeted therapies used in the treatment of cancer can lead to the development of xerosis, but the incidence and relative risk of xerosis have not been ascertained. Objective We conducted a systematic review and metaanalysis of clinical trials, to ascertain the incidence and risk of developing xerosis after taking anticancer drugs. Methods The PubMed (1966-October 2013), Web of Science (January 1998-October 2013), and American Society of Clinical Oncology abstracts (2004-2013) databases were searched for clinical trials of 58 targeted agents. Results were calculated using random or fixed effects models. Results The incidences of all- and high-grade xerosis were 17.9% (95% confidence interval [CI]: 15.6-20.4%) and 1.0% (95% CI: 0.9-1.5%), respectively. The risk of developing all-grade xerosis was 2.99 (95% CI: 2.0-4.3), and it varied across different drugs (P less than .001). Limitations The reporting of xerosis may vary among clinicians and institutions, and the incidence may be affected by age, concomitant medications, comorbidities, and underlying malignancies or skin conditions. Conclusion Patients receiving targeted therapies have a significant risk of developing xerosis. Patients should be counseled and treated early for this symptom to prevent suboptimal dosing and quality of life impairment.